Media Visual Poster Digital Untuk Kebersamaan Karyawan PT Mensa BinaSukses (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
This study addressed the lack of visual communication media within PT Mensa BinaSukses, which resulted in a lack of togetherness. The visual media at the previous event failed to effectively convey the main message to the employees. To solve this problem, the researchers redesigned the visual communication tools, specifically banners and digital posters, using a User-Centered Design approach. The redesign process applied visual communication principles, focusing on color psychology, typography, and structured layouts to enhance message readability. The evaluation revealed a significant increase in the level of employee attendance. The survey results indicated that the redesigned visual media successfully captured employee attention, clarified event information, and fostered a strong sense of togetherness and collaboration with the company.